THE ROLE OF XENOBIOTIC ENZYME GENES OF THE FIRST AND SECOND PHASES IN THE PATHOGENESIS OF FETAL GROWTH RESTRICTION SYNDROME - Mavlyanova, N.N.; Najmutdinova, D.K.; Boboev, K.T. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
biotransformation enzyme of xenobiotics in fetal development restriction syndrome evaluation of allelic variants of ri genes. Materials and Methods: Fetal Development Limitation DNA samples from pregnant women and donor healthy, expressed in dromi, glutathione genes GERTM1 (1p13.3), GSTT1 (22q11.2) and glutathione transferase GSTP1 (IIe 105 Val). In all pregnant women general-clinical, laboratory and functional, molecular-genetic research was carried out. Results: studies have shown that the development of fetal developmental restriction syndrome